Evaluating the behaviour of curcumin nanoemulsions and multilayer nanoemulsions during dynamic in vitro digestion - Silva, Hélder D. (2018)
Nanoemulsions can be used to improve the bioaccessibility of lipophilic bioactive compounds, such as curcumin, being their behaviour highly influenced by their interfacial properties. The effect of chitosan and alginate layers deposition on curcumin nanoemulsions behaviour during in vitro digestion was evaluated using a dynamic gastrointestinal system. Results showed that polyelectrolyte layers deposition improved curcumin antioxidant capacity during in vitro digestion. In addition, multilayer nanoemulsions showed a better control of the rate and extent of lipid digestibility by decreasing free fatty acids release, compared to uncoated nanoemulsions. However, a lower curcumin bioaccessibility was observed for multilayer nanoemulsions. Although cytotoxicity assays revealed that both nanosystems are toxic due to the use of sodium dodecyl sulphate (SDS), nanosystems were 3.3-fold less toxic than SDS itself. This study showed that multilayer nanoemulsions could be used to increase satiety by retarding lipid digestion, which can be important for functional foods development for combating obesity.